Dysregulation of AMPA Receptor Trafficking and Intracellular Vesicular Sorting in the Prefrontal Cortex of Dopamine Transporter Knock-Out Rats - Giorgia Targa; Francesca Mottarlini; Beatrice Rizzi; Damiana Leo; Lucia Caffino; Fabio Fumagalli (Biomolecules, 2023)
Dopamine (DA) and glutamate interact, influencing neural excitability and promoting synaptic plasticity. However, little is known regarding the molecular mechanisms underlying this crosstalk. Since perturbation of DA-AMPA receptor interaction might sustain pathological conditions, the major aim of our work was to evaluate the effect of the hyperactive DA system on the AMPA subunit composition, trafficking, and membrane localization in the prefrontal cortex (PFC). Taking advantage of dopamine transporter knock-out (DAT−/−) rats, we found that DA overactivity reduced the translation of cortical AMPA receptors and their localization at both synaptic and extra-synaptic sites through, at least in part, altered intracellular vesicular sorting. Moreover, the reduced expression of AMPA receptor-specific anchoring proteins and structural markers, such as Neuroligin-1 and nCadherin, likely indicate a pattern of synaptic instability. Overall, these data reveal that a condition of hyperdopaminergia markedly alters the homeostatic plasticity of AMPA receptors, suggesting a general destabilization and depotentiation of the AMPA-mediated glutamatergic neurotransmission in the PFC. This effect might be functionally relevant for disorders characterized by elevated dopaminergic activity.